2006
DOI: 10.1111/j.1601-6343.2006.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Hsp110 expression with caspase‐3 and ‐9 during apoptosis induced by in vivo embryonic exposition to retinoic acid or irradiation in early mouse craniofacial development

Abstract: The findings show a potential function of HSP110 in apoptosis during embryo development. Caspase-3-expressing cells are more numerous than cells expressing caspase-9, especially irradiation-induced apoptotic neural crest cells. This suggests that other caspases, still to be identified, may activate caspase-3 in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The Hsp90 family helped cells resist oxidative stress, prevent apoptosis and regulate reproduction via various ways (Han et al, 2007; Hua et al, 2007; Pan et al, 2009; Zhang et al, 2005). Both Hsp105 and Hsp110 not only played roles in embryonic development but also protected embryos through inhibiting apoptosis (Gashegu et al, 2006; Yamagishi et al, 2002). Apg-1 played an important role following transient forebrain ischemia in the rat brain (Xue et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The Hsp90 family helped cells resist oxidative stress, prevent apoptosis and regulate reproduction via various ways (Han et al, 2007; Hua et al, 2007; Pan et al, 2009; Zhang et al, 2005). Both Hsp105 and Hsp110 not only played roles in embryonic development but also protected embryos through inhibiting apoptosis (Gashegu et al, 2006; Yamagishi et al, 2002). Apg-1 played an important role following transient forebrain ischemia in the rat brain (Xue et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…As regards the physiological apoptosis, the RA‐induced apoptosis is not mediated through caspase‐9 activation, the classical initiator caspase in the mitochondrial apoptosis pathway. However, caspase‐9 activation has been shown in RA‐induced apoptosis within neural crest cells (Gashegu et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, caspase-9 activation has been shown in RA-induced apoptosis within neural crest cells (Gashegu et al 2006). The caspase activation cascade is probably dependent on the type of cells undergoing cell death, as reported by others (Kuida et al 1996(Kuida et al , 1998Haken et al 1998;Varfolomeev et al 1998;Singh et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that Hsp32, Hsp30, Hsp27, Hsp26, Hsp25, Hsp23, and Hsp22 of the sHsps family, 14,23 27 Hsp40 of the Hsp40 family, 28 Hsp60, Hsp62 and Hsp56 of the Hsp60 family, 29 31 HspA1A, HspA1B, HspA2, Grp78, HspA8, HspA9, HspA12B and HspA14 of the Hsp70 family, 32 39 Hsp90AA1, Hsp90AB1, Grp94, and Trap1 of the Hsp90 family, 40 43 and Hsp105 and Hsp110 of the Hsp110 family 17,44 were expressed in embryonic tissues of different animals.…”
Section: Discussionmentioning
confidence: 99%